DEFICIENT OF THE STATE BUDGET OF UKRAINE - Sydor, H. V.; Tkachik, O. I. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
Purpose. Investigation of essence of deficit of the State Budget from the point of view of existing approaches in economic science. Methodology of research. The theoretical and methodological basis of the research is the scientific works of domestic and foreign authors on the research of the essence of the deficit of the State Budget of Ukraine, Internet resources. In the process of research used general and special methods, in particular: monographic – in the implementation of the literary review of the problem under study; systemic and structural analysis – in substantiating different approaches and different points of view before interpreting the essence of the State Budget deficit as a complex economic category. Findings. Generalized theoretical developments of domestic and foreign scientists-economists on the interpretation of the «deficit of the State Budget». At the theoretical level, it has been proved that over the entire period of functioning of Ukraine as an independent state there was an excess of the expenditure part of the State Budget over its revenue. Traced causal relationships, which are important reasons for the appearance of a deficit of the State Budget in Ukraine. The research of those scientists considering the definition of «deficit of the State Budget» from positive and negative sides is considered. It was established that it would assess the financing of the position of the state and the country affecting the budget and tax policy of the balance of payments, the state of the monetary system and the internal order, which allows to identify the deficit of the State Budget. Originality. It is suggested to trace causal relationships, which are important reasons for the occurrence of the deficit of the State Budget in Ukraine. Practical value. The obtained research results are the basis for solving practical problems of the correct scientific approach to understanding this concept at the present stage.